Acute Phase Serum Leptin, Adiponectin, Interleukin-6, and Visfatin Are Altered in Chinese Children With Febrile Seizures: A Cross-Sectional Study - Chen, Jie-ru; Jin, Mei-fang; Tang, Ling; Liu, Yue-ying; Ni, Hong (Frontiers in Endocrinology, 2020)
Adipokines including leptin, visfatin, adiponectin, and IL-6 play multiple roles in the pathophysiology of epilepsy and febrile seizures (FS). The purpose of this study was to determine if leptin, visfatin or adiponectin and IL-6 in serum changed significantly in children with FS, and whether this change helped predict the disease. This prospective cross-sectional study was conducted from January 2017 to December 2018 at the Second Hospital of Wuxi City, Nanjing Medical University, China. The levels of serum leptin, visfatin, adiponectin, and IL-6 in 55 children with FS (FS group) were compared with 42 febrile children without seizure (FC group) and 48 healthy children (HC group) in acute phase. The correlation with clinical indicators was determined by logistic regression analysis. Serum adiponectin and IL-6 levels were significantly higher in the FS group than in the FC and HC groups (p <0.05), but there was no statistical difference between the FC and HC groups. In addition, logistic regression analysis showed that high concentrations of adiponectin and IL-6 were significantly associated with the occurrence of FS. For leptin and visfatin, they were significantly lower in the FS and FC groups than in the normal control group, but there was no statistical difference between the FS and FC groups. Our data suggest that certain adipokines, such as adiponectin and IL-6, can be used as early biomarkers to assist in the early diagnosis of FS.